2005
DOI: 10.2110/palo.2004.p04-67
|View full text |Cite
|
Sign up to set email alerts
|

Decay and Mineralization of Invertebrate Eggs

Abstract: Both the timing and nature of early Metazoan evolution remain controversial, with complementary, and sometimes conflicting, evidence from molecular data and fossil occurrences. Exceptionally preserved embryos from the Neoproterozoic and early Phanerozoic remain an important source of direct evidence: fossil embryos of complex organisms at a relatively advanced stage of development provide a test of hypotheses based on comparative embryology and the evolutionary development of living forms. Understanding how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 37 publications
2
37
0
Order By: Relevance
“…The dry mass contained 120 ppm Ca and 1.3 wt.-% P, comparable to concentrations described for other invertebrate eggs (Martin et al, 2005). Scanning electron microscopic (SEM) mapping of P of an untreated egg in cross-section furthermore revealed an almost uniform distribution of P, however with higher initial P concentrations in the embryonic tissue of the germ area and in some areas of marginal embryonic tissue (Fig.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The dry mass contained 120 ppm Ca and 1.3 wt.-% P, comparable to concentrations described for other invertebrate eggs (Martin et al, 2005). Scanning electron microscopic (SEM) mapping of P of an untreated egg in cross-section furthermore revealed an almost uniform distribution of P, however with higher initial P concentrations in the embryonic tissue of the germ area and in some areas of marginal embryonic tissue (Fig.…”
Section: Resultssupporting
confidence: 72%
“…Experimental phosphatization of eggs was first reported from the shrimp Palaemon elegans, which was subjected to decay as a complete animal for 20 weeks (Briggs and Kear, 1993a). Later studies, which focused on the eggs, demonstrated that it was possible to maintain the external shape of Homarus gammarus, Limulus polyphemus, and Nephrops norvegicus egg cases for at least a year, including surface mineralization mainly as calcium carbonate or as a combination of calcium carbonate and calcium phosphate (Martin et al, 2003(Martin et al, , 2005. Laboratory decay experiments also achieved the replication of the outer morphology of H. gammarus eggs by coating the eggs with pre-existing clay minerals in the presence of metabolizing bacteria (Martin et al, 2004).…”
Section: Hippler Et Al: Experimental Mineralization Of Crustaceanmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data provide direct evidence for microbial biofilms and identification of bacterial taxa involved in decay, pseudomorphing of cell structures, and potential for mineralization that can lead ultimately to exceptional fossilization. We recognize that even when microbes are present, mineralization of animal soft tissue may be produced abiogenically, for example, under conditions of high phosphate concentrations (26)(27)(28). The frequency of these mineralization modes remains to be determined for embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Invertebrate eggs can be quite resistant to decay (Martin et al 2003(Martin et al , 2005) and various structures (mostly associated with ammonoid remains) interpreted as ammonoid eggs have been reported from the Carboniferous (e.g.,?Rhadinites or?Anthracoceras: Landman et al 2010), Triassic ( Ceratites: Müller 1969), Jurassic (Dreyfuss 1933;Wetzel 1959;Eleganticeras: Lehmann 1966, 1990Kachpurites: Baranov 1985;Etches et al 2009;Fig. 5.23) and Cretaceous (Baculitidae gen. et sp.…”
Section: Reproductive Strategy and Egg-layingmentioning
confidence: 99%